Therapeutic approaches against coronaviruses acute respiratory syndrome - Camilla Servidio; Francesco Stellacci (Wiley, 2021)
Abstract Coronaviruses represent global health threat. In this century, they have already caused two epidemics and one serious pandemic. Although, at present, there are no approved drugs and therapies for the treatment and prevention of human coronaviruses, several agents, FDA‐approved, and preclinical, have shown in vitro and/or in vivo antiviral activity. An in‐depth analysis of the current situation leads to the identification of several potential drugs that could have an impact on the fight against coronaviruses infections. In this review, we discuss the virology of human coronaviruses highlighting the main biological targets and summarize the current state‐of‐the‐art of possible therapeutic options to inhibit coronaviruses infections. We mostly focus on FDA‐approved and preclinical drugs targeting viral conserved elements.